Response surface methodology optimization and kinetics study for anthracene adsorption onto MIL-88(Fe) and NH2-MIL-88(Fe) metal-organic frameworks. Issue 1 (March 2021) - Zango, Z U; Ramli, A; Jumbri, K; Sambudi, N S; Isiyaka, H A; Abu Bakar, N H H; Saad, B
Abstract: The experimental adsorption of Anthracene (ANT), a model polycyclic aromatic hydrocarbon (PAHs) was optimized using central composite design (CCD) of response surface methodology (RSM). MIL-88(Fe) and NH2 -MIL-88(Fe) Metal-organic frameworks (MOFs) were employed as the potential adsorbents. The model was described as the significant according to the analysis of variance (ANOVA) for the statistical fittings of R 2 (0.991 and 0.992), and adequate precision (43.55 and 47.82) with the lack of fit F-values (2.15 and 1.59) for the MIL-88(Fe) and NH2 -MIL-88(Fe) respectively. The highest adsorption efficiency achieved were 99.55 and 95.67% for the MIL-88(Fe) and NH2 -MIL-88(Fe) respectively based on the RSM optimized conditions. The pseudo-second-order kinetic model has been described as the best mechanism for the adsorption process.